Separatist and Terrorist Movements in Papua: The Challenges of Social Disaster Management and the Important Role of Human-Made Disaster Intelligence - Maharani, Tiara Devi; Sarjito, Aris; Marnani, Christine Sri; Almubaroq, Hikmat Zakky; Falefi, Reinpal (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
The Papua secessionist movement hinders Indonesia’s stability efforts. The government has implemented measures, deploying intelligence for managing social crises as defined by Law 24 of 2007 on Disaster Management. The present study examines the separatist movement in Papua, its resultant societal upheaval, and the crucial role of intelligence in mitigating this societal crisis. The study explores applying Human-Made Disaster Intelligence, using AI and data tech, to mitigate risks in the Papua case. This study employs a literature review with 26 sources to explore challenges posed by separatist and terrorist movements in Papua. Data is gathered from official sources, excluding personal websites and social media. The study was conducted from January to March 2023. Data analysis utilizes descriptive narratives to qualitatively explore separatist and terrorist movements, social disasters, intelligence, and the Papua region. The research findings demonstrate that the separatist movement in Papua has resulted in a significant societal calamity, causing conflicts, casualties, and economic challenges. Man-made disaster intelligence is proposed to manage social disasters by collecting and analyzing data related to separatist activities. Intelligence plays a crucial role in detecting and mitigating risks associated with separatism, offering preventive and remedial measures. Challenges include limited resources and the need for collaboration among intelligence agencies. Strategic measures to enhance intelligence involve increased resources, collaboration, transparency, and the integration of Artificial Intelligence (AI) for data analysis. The complexity of using AI in countering separatist movements requires careful consideration of data sources, collection methods, and reliability measures.